MODEL PENDIDIKAN ADAB, TAHFIZH AL QURAN BAGI MAHASISWA: PENGALAMAN PENDIDIKAN TINGGI ISLAM INDONESIA - Isa Al Ghani, Yan; Katni Katni; Umi Purnawati; Yuliana Rahma (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
Islamic higher education plays a crucial role in formulating the ideal character education concept for its graduates. Universities not only serve as a place for transferring knowledge but are also responsible for shaping the character of their students. One strategy that can be implemented is the dormitory system. This research, in the context of this study, uses a qualitative approach, a type of field research. The key instrument of this research is the researcher herself. Data collection was carried out through interviews, observation, and documentation. Data analysis was carried out through reduction, display, and verification. Data validation was carried out using triangulation. Research at Mahad Aly Al Furqon shows that effective character education strategies include: student dormitory placement with support from facilities and funding, the creation of contracts and regulations that are mutually adhered to, the habituation and supervision of positive activities, scientific studies, scientific discussions, community outreach, and entrepreneurial training and practice. As a result, students formed through this program demonstrate positive character traits such as discipline, politeness, respect, clean living, courage, responsibility, independence, caring, helpfulness, perseverance, and tenacity.